1876. Patient- and Hospital-Level Factors and Outcomes Associated With Treatment of Asymptomatic Bacteriuria in Hospitalized Patients: A Multi-Hospital Cohort Study. (26th November 2018) - Petty, Lindsay; Conlon, Anna; Vaughn, Valerie; Nielsen, Daniel; Kaye, Keith; Malani, Anurag; Thyagarajan, Rama; Osterholzer, Danielle; Eschenauer, Gregory; Flanders, Scott; Gandhi, Tejal N
Abstract: Background: Treatment of asymptomatic bacteriuria (ASB) is a major driver of inappropriate antibiotic use and an important target for antimicrobial stewardship. We identified patient- and hospital-level factors associated with treatment of ASB and its impact on patient outcomes. Methods: In this retrospective cohort study, detailed data were abstracted from the medical record of adult non-ICU patients hospitalized with a positive urine culture (Ucx) between January 2016 and February 2018 at 46 Michigan hospitals. Exclusions included pregnancy, urologic surgery or abnormality, immune-compromise, or concomitant infection. ASB was defined as a positive Ucx without signs or symptoms attributable to a urinary tract infection (UTI). The treatment group received ≥1 antibiotic dose. Patient outcomes included mortality, readmissions, Clostridium difficile infection, and emergency room visits. Patient and hospital factors associated with ASB treatment were evaluated using logistic generalized estimating equation models; patient outcomes were inverse probability of treatment weighted. Results: Of 2, 733 included patients with ASB, 82.9% ( n = 2, 266) were treated with antibiotics for a median 7 days (IQR 4, 9). Ceftriaxone (71.1%) was the most frequent initial therapy; fluoroquinolones (33.2%) were most common at discharge. In the multivariable model, patient variables associated with ASB treatment included: increased age, dementia, positive urinalysis, incontinence, indwelling urinary catheter, and nonambulatory status (Figure 1). Hospitals varied (Figure 2), but those that required a documented indication for antibiotics in the order or medical record had lower ASB treatment rates (OR = 0.5). There was no difference in patient outcomes for patients treated vs. not treated with antibiotics. Conclusion: Antibiotic treatment of ASB, often broad-spectrum, is widespread. Certain patient characteristics (including advanced age, nonambulatory, dementia, and incontinence) and the misinterpretation of test results (including overemphasis of the urinalysis) drive clinicians to treat ASB. Requiring documentation of antibiotic indication may decrease inappropriate treatment. Future interventions may be more effective by incorporating these drivers of ASB treatment. Disclosures: All authors: No reported Disclosures.